Observation of universal dynamics in an isolated one-dimensional Bose gas far from equilibrium - Erne, Sebastian; Bücker, Robert; Gasenzer, Thomas; Berges, Jürgen (Arxiv, 2018)
We provide experimental evidence of universal dynamics far from equilibrium during the relaxation of an isolated one-dimensional Bose gas. Following a rapid cooling quench, the system exhibits universal scaling in time and space, associated with the approach of a non-thermal fixed point. The time evolution within the scaling period is described by a single universal function and scaling exponent, independent of the specifics of the initial state. Our results provide a quantum simulation in a regime, where to date no theoretical predictions are available. This constitutes a crucial step in the verification of universality far from equilibrium. If successful, this may lead to a comprehensive classification of systems based on their universal properties far from equilibrium, relevant for a large variety of systems at different scales.